Simalungun Mardingding Protestant Christian Church Database Design, Silimakuta District, Simalungun Regency - Damanik, Romanus; Sipayung, Tiara Julia (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2021)
The Simalungun Protestant Christian Church (GKPS) is a Christian Church of the Simalungun region initiated by the zendelling (evangelist) of the Rheinische Missionsgesellschaft (RMG), a German gospel preaching body as part of its efforts to spread the gospel to the Simalungun Tribe. Since the 1900s RMG established churches in Simalungun as part of huria Kristen Batak Protestant (HKBP) using Toba as the language of instruction. This independence continued until the HKBP congregation in Simalungun bathed itself into one district until finally totally independent to become GKPS and provide services for the surrounding environment in various fields (not just religious services). Of the many Protestant Christian Churches in Indonesia, one of them is the Simalungun Protestant Christian Church (GKPS) Resort Mardinding. This church is a place of worship and gathering of Protestant Christians. This church has many people, but not all tribes are in it. There are currently 423 KK. The provision of information to the people is currently still manual and still uses the announcement affixed to the notice board and also through the announcement from the church administrator who was in charge at the time of the service, this announcement could not contain all the necessary information. Researchers took a case study from GKPS Mardinding so that information systems can be developed using technology that is developing today, namely using websites to store information faster and more accurately.